Efisiensi Sistem Tunjangan Kesehatan Karyawan PT X - Hartono, Vicky; palit, herry christian (Jurnal Titra, 2015)
PT X is a manufacture company that provides medical facilities for its permanent employee in form of medical benefits. The medical benefits claim proposed by the employees will be processed in PT Xâs medical benefits system. The company requires that at least 98% of the claims are processed on the same day as the day those claims are proposed. That requirement can only be fulfilled with overtime work. The average of overtime work per month per admin is 14 hours. The improvement of the efficiency can be done by doing enhancement of the approval and revise processes of the previous medical benefits system. The enhancement is done by creating unique key and barcode for each medical claim, so that each of the new claim form is going to have unique key and barcode. HR admin would be able to do scan barcode process that would accelerate PT Xâs medical benefits system. The result of the implementation of this enhancement is the acceleration of medical benefits system of PT X. The implementation results in the decrease of the process time as much as 31% of the prior condition and the investment fund will have returned in less than three months.